Quality and Chemical Composition of Organic and Non-Organic Vetiver Oil - Asep Kadarohman; Ratnaningsih Eko S.; Gebi Dwiyanti; Lela Lailatul K.; Ede Kadarusman; Ahmad Nur F. (Universitas Gadjah Mada, 2014)
Vetiver oil (Vetiveria zizanoides) has been used as perfume materials, cosmetics, fragrance soaps, anti-inflammation, repellent, and insecticidal agents. Organic vetiver oil has higher economical value than non-organic vetiver oil and it has been regarded to be able to compete in the global market. Therefore, studies have been carried out using 1 hectare of land and the first generation of organic vetiver oil has produced 0.57% of yield, greater than non-organic (0.50%). The quality of organic and non-organic vetiver oil was analyzed by Indonesian Standard (SNI) parameter, pesticide residue test, chemical composition by GC/MS, and the appearance of vetiver root. In general, the result of organic and non-organic vetiver oil has fulfilled the national standard; the quality of organic vetiver oil was better than non-organic one. Physically, the appearance of organic vetiver root was better than non-organic vetiver root; organic vetiver root was denser, more appealing, and did not have any black spots. The pesticide residue of organic vetiver oil was lower than non-organic vetiver oil. Based on SNI test, vetiverol (oxygen compounds) in organic vetiver oil was higher than non-organic vetiver oil.